The synthesis of boronic-imine structured compounds and identification of their anticancer, antimicrobial and antioxidant activities - Salih Pasa; Safa Aydın; Sadık Kalaycı; Mehmet Boğa; Metin Atlan; Murat Bingul; Fikrettin Şahin; Hamdi Temel (Elsevier, 2016)
Boronic acid compounds with different substituted groups were handled to synthesize various ligands encoded as B1, B2, B3, B4, B5, B6, B7 and B8. B5 and B7 were tested for the cytotoxic activity against the prostate cancer cells and it was found that the cell viability of cancer cells was decreased while most of the healthy cells could still be viable. 5 µM solutions of B5 and B7 decreased the cell viability to 33% and 44% whereas healthy cells were 71% and 95%, respectively, after treatment. Antimicrobial properties were explored against the bacterial and fungal microorganisms with B1, B5 and B7. The inhibition zones were evaluated for all boronic structures, and the growth inhibition zones were determined in a range of 7-13 mm diameter for different microorganism species. Staphylococcus aureus was the common microorganism that three boronic compounds with imine ligands showed the activity. Antioxidant features of B2, B3, B4, B5, B6, B7 and B8 were investigated by different processes such as Beta-carotene bleaching (BCB), 2,2-diphenyl picryl hydrazyl (DPPH), 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) and CUPric reducing antioxidant capacity (CUPRAC) methods. Significant antioxidant activity was achieved by the phenyl boronic based ligands and these compounds demonstrated as much activity as standards (α-Toc and BHT). In addition, all structures were applied properly without any decomposition during the experiments. They were rather stable both in aqueous media and solid state.